A new genus and species of high intertidal barnacle (Cirripedia, Tetraclitidae) from Baja California Sur, México - Gomez-Daglio, Liza; van Syoc, Robert (Zootaxa, 2006)
A new genus and species, Lissaclita melaniae (Tetraclitidae), is described from the Gulf of California, Baja California Sur, Mexico. Lissaclita has a secondarily divided single row of parietal tubes without septa, lack of tubes in the radii, diametric shell growth, and a membranous basis. This combination of characters does not agree with any currently described subfamily within the Tetraclitidae. Lacking a detailed phylogenetic analysis of the entire family, we place the new genus in the Tetraclitidae without assigning it to a subfamily.